CONSISTENCY OF THE PROVISIONS ON THE ALL-RUSSIAN CIVIL IDENTITY CONTAINED IN THE DOCTRINAL DOCUMENTS ON THE STATE NATIONAL POLICY OF RUSSIA AND THE REPUBLICS-SUBJECTS OF THE FEDERATION - O. Yu. Yakhshiyan (Вестник университета, 2021)
The article contains a comparative analysis of doctrinal documents in the field of state national policy at the federal and regional-republican levels for consistency of provisions on the Russian nation and all-Russian civil identity. The paper considers in detail the interpretation of the relevant provisions in the Strategy of the State National Policy of the Russian Federation for the period up to 2025. The author draws on the publications of Russian ethnopolitologists, which study the practice of politicizing the titular ethnic identity in a number of republics of the Russian Federation with the prospect of identifying ethnic and regional identities. Reference to the corpus of concepts (strategies) of national policy in the republics – subjects of the Russian Federation allowed us to identify the accepted provisions on the all-Russian civil identity contained in the federal Strategy, and the republican-ethnic accents in its interpretation, and the provisions that have not yet been picked up. In particular, the analysis of doctrinal documents of the republics showed that one of the most important provisions of the Federal Strategy on Preservation of Russian Cultural Dominance (a Single Cultural-Civilizational Code), common to all the peoples of Russia, as the basis of all-Russian civil identity has not received a response in concepts (strategies) of the Russian republics.